Chances are... [compact disc, unabridged] : a novel - Russo, Richard, 1949- (Random House Audio, 2019)
One beautiful September day, three sixty-six-year-old men convene on Martha's Vineyard, friends ever since meeting in college, and must puzzle out a lingering mystery from the summer of 1971.